2004
DOI: 10.1080/00016480410016586
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cochlear Blood Supply with Mitochondrial DNA Common Deletion in Presbyacusis

Abstract: The high incidence of the mtDNA4977 deletion in the temporal bones of presbyacusis patients suggests a correlation between the mtDNA4977 deletion and presbyacusis. Hypoxia of the cochlea may cause the mtDNA4977 deletion and other mtDNA mutants and furthermore may cause a reduction in mitochondrial oxidative phosphorylation and decreased function of the acoustic neural system. The symptoms of presbyacusis may occur when the function of the acoustic neural system is impaired as a result of abnormal mtDNA metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 8 publications
2
35
0
Order By: Relevance
“…Damaged mitochondrial DNA may cause reduced oxidative phosphorylation, which may lead to neural dysfunction in the inner ear. A study by Dai et al [12] also suggested that damaged mitochondrial DNA may lead to anatomic changes of the inner ear, more severe narrowing of the vaso nervorum in the internal auditory meatus in temporal bones with a mitochondrial DNA deletion. Damaged mitochondrial DNA has also been linked to a greater rate of apoptosis of certain cells in the inner ear in a study by Pickles [13].…”
Section: Discussionmentioning
confidence: 99%
“…Damaged mitochondrial DNA may cause reduced oxidative phosphorylation, which may lead to neural dysfunction in the inner ear. A study by Dai et al [12] also suggested that damaged mitochondrial DNA may lead to anatomic changes of the inner ear, more severe narrowing of the vaso nervorum in the internal auditory meatus in temporal bones with a mitochondrial DNA deletion. Damaged mitochondrial DNA has also been linked to a greater rate of apoptosis of certain cells in the inner ear in a study by Pickles [13].…”
Section: Discussionmentioning
confidence: 99%
“…One specific mtDNA deletion, mtDNA4,834, has been linked to AHL in rodents [59]. The equivalent mutation, mtDNA4,977, deletion in human has also been identified, using archived temporal bones from patients with presbycusis [60][61][62]. Interestingly, consistent with a causal role for mtDNA mutations in ARHL, mice carrying a mutation in the exonuclease domain of the nucleus-encoded catalytic subunit of the mtDNA polymerase gamma (POLG), accumulated mtDNA mutations and displayed premature onset of ageingrelated phenotypes, including HL [63].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…There is also loss of nerve fibres and neural elements. [14] The reduction in blood flow leads to formation of Reactive Oxygen Metabolites (ROM), which affects inner ear structure and damages mitochondrial DNA. [14] Mitochondrial DNA deletions lead to deafness.…”
Section: Discussionmentioning
confidence: 99%
“…[14] The reduction in blood flow leads to formation of Reactive Oxygen Metabolites (ROM), which affects inner ear structure and damages mitochondrial DNA. [14] Mitochondrial DNA deletions lead to deafness. Researchers observed that diminished flow in capillaries of basal turn of cochlea correlates with higher frequency hearing loss in elderly.…”
Section: Discussionmentioning
confidence: 99%